2019
DOI: 10.1109/tbme.2018.2845865
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Convulsive Seizures Using a Wearable Accelerometer Device

Abstract: Epileptic seizure detection requires specialized approaches such as video/electroencephalography monitoring. However, these approaches are restricted mainly to hospital setting and requires video/EEG analysis by experts, which makes these approaches resource- and labor-intensive. In contrast, we aim to develop a wireless, remote monitoring system using a single wrist-worn accelerometer sensor, which is sensitive to multiple types of convulsive seizures and is capable of detecting seizures with short duration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…The proposed quantitative method yields a nonlinear projection of the three‐dimensional (3D) rhythmic limb movement into a numerical score, thus allowing reliable distinction between GTCS and convulsive PNES with less experience. In addition, wearable ACM‐based devices can be used reliably for long‐term continuous monitoring of patients; therefore, in the future, the clinical utility of the proposed approach can be further enhanced into a wearable device by the incorporation of automated algorithm for detection and differentiation of GTCS and convulsive PNES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed quantitative method yields a nonlinear projection of the three‐dimensional (3D) rhythmic limb movement into a numerical score, thus allowing reliable distinction between GTCS and convulsive PNES with less experience. In addition, wearable ACM‐based devices can be used reliably for long‐term continuous monitoring of patients; therefore, in the future, the clinical utility of the proposed approach can be further enhanced into a wearable device by the incorporation of automated algorithm for detection and differentiation of GTCS and convulsive PNES.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometers (ACMs) have been shown to be an effective tool for detection of convulsive seizures especially, GTCS . In our previous work, we showed that ACMs can be used reliably for the detection of convulsive PNES events. However, differentiation of convulsive PNES and GTCS requires identification of unique features that can distinguish epileptic and nonepileptic motor activity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of limb-worn accelerometry sensors that can record movements is one such avenue that is being explored by a number of groups. [13][14][15] Our previous research has shown that the evolutionary pattern of the frequencies of rhythmic movement artifacts on EEG during PNES differs from that of ES. 16 Convulsive PNES were demonstrated to display a characteristic pattern of rhythmic movement artifact that remains stable over time during the event, whereas the EEG activity during convulsive ES tends to evolve throughout.…”
Section: Introductionmentioning
confidence: 99%
“…The use of limb‐worn accelerometry sensors that can record movements is one such avenue that is being explored by a number of groups . Our previous research has shown that the evolutionary pattern of the frequencies of rhythmic movement artifacts on EEG during PNES differs from that of ES .…”
Section: Introductionmentioning
confidence: 99%